2016
DOI: 10.1590/1807-3107bor-2016.vol30.0028
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of new MTA-based cement formulations on fibroblast-like MDPL-20 cells

Abstract: The present study aimed at evaluating the cytotoxic effects of a novel cement called CER on periodontal fibroblast-like cells of mice , in comparison with different formulations of Mineral Trioxide Aggregate (MTA), by means of the cell viability test (MTT) and cell morphology analysis. Thirty-two round-shaped samples were fabricated with the following cements: white MTA, white and gray CER and experimental white MTA. The samples were immersed in serum-free culture medium for 24 hours or 7 days (n = 16). The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The most important requirement for better efficacy of biomaterials like MTA is their biocompatibility with the host tissue upon implantation ( 13 , 14 ). The clinical success of a biomaterial depends upon the ability to produce the required effect of cellular or tissue response ( 15 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important requirement for better efficacy of biomaterials like MTA is their biocompatibility with the host tissue upon implantation ( 13 , 14 ). The clinical success of a biomaterial depends upon the ability to produce the required effect of cellular or tissue response ( 15 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…This tissue is continuous with the gingival connective tissue and consists of fibroblasts that are the principal cells producing and forming collagen fibers and mesenchymal cells with the capacity to differentiate into cementoblasts and osteoblasts. Therefore, the primary gingival fibroblasts are appropriate for the evaluation of the toxicity of this material ( 13 , 23 , 24 ). On the other hand, fibroblasts are the most abundant cells of the pulp and periodontal ligament connective tissue ( 1 ); therefore, during procedures such as vital pulp therapy, apexification and during their use as a retrofilling materials during apicoectomy procedures, MTA comes into contact with these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility of MTA alone has been reported to be favourable with dental pulp and fibroblast cells in previous literature. 13,14 The cytotoxic reactions that occur in the host tissues with the addition of these nanoparticles needs to be evaluated. The cytotoxicity of the experimental groups was analysed using the MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Garcia et al [16] investigated the cytotoxic effects of the CER on fibroblast-like MDPL-20 cells and found that at the 24-hour period, the CER cement presented the highest cytotoxic effects on the fibroblast-like cells when compared to conventional white MTA; however, at the 7-day period, the cytotoxicity of CER decreased and reached similar parameters to that of the white MTA. Since this was an in vitro study, new studies are needed to analyze these new MTA-based cement formulations.…”
Section: Introductionmentioning
confidence: 99%